Refugee Politics in the Middle East and North Africa Human Rights, Safety, and Identity - Ullah, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Ahsan Ullah provides an insightful analysis of migration and displacement in the Middle East and North Africa. He examines the intricate relationship of these phenomena with human rights, safety concerns and issues of identity crisis and identity formation.
Keywords: Africa—Politics and government; Economic development; Middle East—Politics and government; Social policy; Emigration and immigration; International relations; African Politics; Development Studies; Middle Eastern Politics; Social Policy; Migration; International Relations